Pengaruh Faktor Budaya dan Kecemasan terhadap Kepatuhan Siswa SMP Mengikuti Vaksinasi Covid-19 di Kampung Degen Distrik Teluk Patipi - Santoso Budi Rohayu; Meriam Christiani Hukubun; Bahtiar Yusuf (Jurnal Keperawatan, 2023)
The ongoing Covid-19 pandemic means that people, especially teenagers, still have to implement health protocols. However, face-to-face learning has begun to be implemented in various schools with the obligation to wear masks, wash hands, maintain a distance of 1 meter, limit mobilization and carry out Covid-19 vaccinations. The government's Covid-19 Vaccine Program for the entire Indonesian population has generated various responses in society. The Covid-19 vaccine is currently available for teenagers who take part in face-to-face learning. However, in practice, there are still many teenagers who experience anxiety so they do not comply with the Covid-19 vaccination. This research aims to determine the influence of cultural factors and anxiety on junior high school students' compliance with the Covid-19 vaccination in Degen Village, Teluk Patipi District. The research method that will be used is an analytical survey using a cross sectional research design. The sampling technique used in this research was purposive sampling with a population of 128 and the respondents for this research were 97 students of SMP Negri 2 Degen. Bivariate analysis used the Chi-square test using SPSS with a significance level of α=0.05 (5%) with a nominal data scale. The research results show that there is an influence of cultural factors and anxiety on junior high school students' compliance with the Covid-19 vaccination using SPSS 26.0 descriptive test with a 2 tailed sigh result of p=0.00 with a=0.05 which means the hypothesis is accepted. Cultural factors and anxiety have a significant influence on participation in vaccination. Cultural factors, including the beliefs and customs of indigenous Papuans (OAP), which are still strong and inaccurate information regarding vaccines, make teenagers anxious and ultimately have a negative response and will have a psychosomatic impact so that they cannot receive the vaccine. Proper education and effective communication from the government and trusted sources are critical in addressing this issue.